Hepatitis A and hepatitis B infection risk among employees at schools for disabled pupils - Felix Lang; Klaus Schoene; Felix Goessler; Dirk-Matthias Rose; Peter Kegel (Scientific Reports, 2022)
Abstract Aim of this project was to assess occupational biological hazards with regard to the risk of hepatitis A (HAV) and hepatitis B (HBV) and the need for occupational health care in schools for pupils with special needs. Teachers and educational specialists were surveyed about activities potentially providing exposure to biological agents and their individual immune status regarding HAV and HBV by a detailed questionnaire. Descriptive analyses, group comparisons and logistic regression were performed to identify factors influencing the HAV and HBV immune status. 1398 teachers and educational specialists took part. 1381 respondents reported having physical contact with pupils at work (98%). Daily contact was reported by up to 84% of all employees. Being scratched, bitten or spat at was reported by up to 93%. Hazardous activities are performed by both teachers and educational specialists. The vaccination rate was reported to be 58% for HAV and 64% for HBV. In regression analyses, failing to receive vaccine counselling [HAV: aOR 0.36 (95% CI 0.28; 0.46; p < 0.001), HBV: aOR 0.43 (95% CI 0.33; 0.55; p < 0.001)] or non-participation in infection prevention instruction [HBV: aOR 0.54 (95% CI 0.39; 0.75; p < 0.001)] were found to be significant predictors of low vaccination rates. Employees who are at risk due to occupational exposure should be instructed about infection prevention and vaccination against HAV and HBV.